2016
DOI: 10.4238/gmr.15017273
|View full text |Cite
|
Sign up to set email alerts
|

Role of single nucleotide polymorphisms of DNA repair genes in susceptibility to pancreatic cancer in Chinese population

Abstract: ABSTRACT. We conducted a case-control study to investigate the role of ERCC1-ERCC5 gene polymorphisms in the risk of pancreatic cancer. This study included 195 patients who were newly diagnosed with histopathologically confirmed primary pancreatic cancer, and 254 controls were recruited from Sir Run Run Shaw Hospital, between January 2012 and December 2014. Genotyping of ERCC1 rs3212986 and rs11615, ERCC2 rs13181, ERCC3 rs4150441, ERCC4 rs6498486, and ERCC5 rs2094258 polymorphisms was carried out using polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The final meta-analysis included 47 articles. There were 22 articles with 12,833 cases and 151,86 controls for rs1047768 T>C [ 7 9 , 12 , 14 31 ], 14 studies with 11,327 cases and 12,684 controls for rs2296147 T>C [ 9 11 , 13 , 18 , 24 , 26 28 , 32 – 37 ], 11 studies with 5,898 cases and 7,448 controls for rs2227869 G>C [ 8 , 9 , 14 , 17 , 18 , 20 , 22 , 25 , 38 40 ], 17 studies with 9,826 cases and 10,552 controls for rs2094258 C>T [ 10 , 11 , 18 , 24 , 26 28 , 34 – 37 , 41 – 46 ], 21 studies with 10,369 cases and 11,207 controls for rs751402 C>T [ 10 , 13 , 24 , 26 29 , 31 , 32 , 36 , 37 , 42 45 , 47 52 ], and 14 studies with 10,873 cases and 12,535 controls for rs873601 G>A [ 9 11 , 18 , 24 , 26 28 , 32 , 34 , 36 , 52 54 ]. A flow chart summarizing the process of relevant study identification is shown in Figure 1 , and the study characteristics are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The final meta-analysis included 47 articles. There were 22 articles with 12,833 cases and 151,86 controls for rs1047768 T>C [ 7 9 , 12 , 14 31 ], 14 studies with 11,327 cases and 12,684 controls for rs2296147 T>C [ 9 11 , 13 , 18 , 24 , 26 28 , 32 – 37 ], 11 studies with 5,898 cases and 7,448 controls for rs2227869 G>C [ 8 , 9 , 14 , 17 , 18 , 20 , 22 , 25 , 38 40 ], 17 studies with 9,826 cases and 10,552 controls for rs2094258 C>T [ 10 , 11 , 18 , 24 , 26 28 , 34 – 37 , 41 – 46 ], 21 studies with 10,369 cases and 11,207 controls for rs751402 C>T [ 10 , 13 , 24 , 26 29 , 31 , 32 , 36 , 37 , 42 45 , 47 52 ], and 14 studies with 10,873 cases and 12,535 controls for rs873601 G>A [ 9 11 , 18 , 24 , 26 28 , 32 , 34 , 36 , 52 54 ]. A flow chart summarizing the process of relevant study identification is shown in Figure 1 , and the study characteristics are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[13] Ying et al reported no significant associations between ERCC2 rs13181 polymorphism and PC risk. [29] However, Sileng et al indicated that ERCC2 rs13181 polymorphism exposed higher risk to PC. [30] In addition, McWilliams et al indicated that ERCC2 rs13181 polymorphism was associated with PC risk.…”
Section: Discussionmentioning
confidence: 99%